1995
DOI: 10.1093/clinids/20.supplement_2.s304
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Putative Periodontal Pathogens in Subgingival Specimens by 16S Ribosomal DNA Amplification with the Polymerase Chain Reaction

Abstract: The utility of the 16S ribosomal RNA-based polymerase chain reaction (PCR) for detection of Actinobacillus actinomycetemcomitans, Bacteroides forsythus, Campylobacter rectus, Eikenella corrodens, Porphyromonas gingivalis, Prevotella intermedia, and Treponema denticola was examined and compared with that of anaerobic culture. Primer pairs consisting of 20-27 nucleotides amplified 404- to 688-bp regions of 16S ribosomal RNA genes of these organisms. This method had a lower detection limit of 50 target cells in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
125
0
5

Year Published

1997
1997
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 147 publications
(138 citation statements)
references
References 3 publications
5
125
0
5
Order By: Relevance
“…Organisms such as Actinobacillus actinomycetemcomitans, Fusobacterium nucleatum, Porphyromonas gingivalis, Prevotella intermedia or Eikenella corrodens have been considered to have a role in periodontal disease (9,11). Studies have demonstrated a strong correlation between the presence of putative periodontal organisms and the destruction of periodontal tissues (10).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Organisms such as Actinobacillus actinomycetemcomitans, Fusobacterium nucleatum, Porphyromonas gingivalis, Prevotella intermedia or Eikenella corrodens have been considered to have a role in periodontal disease (9,11). Studies have demonstrated a strong correlation between the presence of putative periodontal organisms and the destruction of periodontal tissues (10).…”
Section: Introductionmentioning
confidence: 99%
“…Polymerase chain reaction (PCR) has been used for direct identification of periodontal pathogens in subgingival specimens (3,11) and also for elucidating the role of specific bacteria in the periodontal disease because of the ability to accurately detect species in mixed populations. 16S rRNA gene amplification has been used for detection of microorganisms that cannot be cultivated but these methods have given crossreactions with related organisms (11).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The DNA was resuspended in TE buffer (10 mM Tris-HCl, 0.1 mM EDTA, pH 7.5, with 10 μg/mL RNAse). Molecular microbial identification was carried out by PCR with specific primers for Aggregatibacter actinomycetemcomitans, 25 Porphyromonas gingivalis, 26 Tannerella forsythia, 27 Candida albicans, 24 Candida glabrata, 24 Candida tropicalis, 24 and Candida dubliniensis. 28 PCR amplification was performed with a thermocycler AmpliTherm TX96 Gradient (Axygen, NY, USA) under thermal conditions specific for each pair of primers.…”
Section: Microbiological Evaluation -Polymerase Chain Reaction (Pcr)mentioning
confidence: 99%
“…The 16S rRNA gene from strain B106 T was PCR amplified in triplicate using the primers D134 (59-GAGTTTGAT-CCTGGCTCAGG-39) and D57 (Slots et al, 1995) (Invitrogen). The PCR products were pooled, purified and desalted, and subjected to direct DNA sequence analysis.…”
Section: Phylogenetic Analysismentioning
confidence: 99%